Cognitive conflict resolution during psychotherapy: Its impact on depressive symptoms and psychological distress. (2nd January 2019) - Paz, Clara; Montesano, Adrián; Winter, David; Feixas, Guillem
Abstract: Objective : The aim of this study was to assess the resolution of cognitive conflicts (CCs) within a randomized controlled trial testing the differential efficacy of group cognitive behavioral therapy (CBT) plus an individually tailored intervention module focused on CCs vs. group plus individual CBT, and to determine whether CC resolution was related to improvement in symptoms and psychological distress.Methods : The data come from 104 adults meeting criteria for major depressive disorder and/or dysthymia. Change in scores on the Beck Depression Inventory-II and Clinical Outcomes in Routine Evaluation-Outcome Measure was assessed at the end of treatment and at three-month follow-up. Outcomes were compared between those participants who resolved their CCs and those who maintained them using three-level multilevel growth models.Results : CC resolution did not depend on treatment allocation. Participants who resolved their CCs acquired greater benefits with regards to reduction of depressive symptoms and psychological distress than those who maintained their conflicts.Conclusions : CC seems to be a relevant notion to take into consideration to understand symptom improvement. Further research on CC might lead to the advancement of treatments which involve conflict resolution as a change mechanism.